Association of rs2910164 in miR-146a with type 2 diabetes mellitus: A case–control and meta-analysis study - Chang, Wei-Wei; Wen, Li-Ying; Zhang, Liu; Tong, Xin; Jin, Yue-Long; Chen, Gui-Mei (Frontiers in Endocrinology, 2022)
Objective: Several studies have shown that miR-146a rs2910164 (C>G) is associated with type 2 diabetes mellitus (T2DM) susceptibility, but the results are still controversial. This study is divided into two parts, and one is to explore the relationship between miR-146a rs2910164 polymorphism and the genetic susceptibility of T2DM in Chinese Han population. Second, a meta-analysis on the basis of a larger sample size was used to determine whether this is a susceptibility gene for T2DM. Methods: A case-control study including 574 T2DM patients and 596 controls was used to evaluate the association of miR-146a rs2910164 polymorphism with the risk of T2DM in Chinese Han People adjusting for age, gender, and BMI. Then, we systematically searched studies investigating the correlation between miR-146a rs2910164 polymorphism and T2DM susceptibility published before April, 2022 from Pub Med, web of science, Wanfang, and China National Knowledge Infrastructure database, and a meta-analysis including six studies was carried out. The results were expressed by odds ratio (OR) and its 95% confidence interval (95%CI). Results: In a case-control study, we found that there were no statistical differences in genotype frequencies between T2DM and control group. Subgroup analysis showed that compared with the CC genotype, CG+GG genotype was associated with a decreased risk of T2DM in the subgroup of individuals ≥65 years old (OR = 0.75; 95% CI:0.58–0.98; Padjusted=0.032) and BMI<18.5 (OR = 0.16; 95% CI:0.03–0.89; Padjusted=0.037). In overall meta-analysis, significant heterogeneity was detected. No significant association between miR-146a rs2910164 polymorphism and T2DM was observed in all genetic models under random-effects models. Subgroup analysis revealed that there was a significant difference in genotype frequencies between the T2DM and control group in recessive model (CC vs. CG + GG: OR = 1.79; 95% CI: 1.08–2.96; PQ=0.307, I2=4.0%) and homozygote model (CC vs. GG: OR = 1.79; 95% CI: 1.07–3.00; PQ=0.216, I2=34.7%) in Caucasians. Conclusion: The results of our study demonstrate that the miR-146a rs2910164 polymorphism might have ethnicity-dependent effects in T2DM and may be related to T2DM susceptibility in Caucasians.